Hierarchical task offloading in heterogeneous cellular network:modeling and optimization - Lindong ZHAO; Wenqin ZHUANG; Jianxin CHEN; Liang ZHOU (Tongxin xuebao)
To improve the efficiency of computation offloading,a hierarchical task offloading framework based on device-to-device (D2D) communication,mobile edge computing and cloud computing was proposed,in which cooperative D2D relay technology was introduced to assist users to access remote computing resources.Considering the negative effects of uplink channel congestion,limited edge computing capability,D2D reuse interference and backhaul delay of cloud computing in the multi-user scenario of the proposed framework,a game theory based offloading scheduling and load balancing scheme was developed by fully taking advantage of the computing and communication resources in the proposed framework.The simulation results demonstrate that the proposed scheme can effectively reduce end-to-end delay and offloading energy consumption,and also has good stability even when the network resources are limited.